On the Melodic Nature of Lad Combinations in Traditional Music - Muminova Dilfuzakhon Numonovna (International Journal on Integrated Education, 2021)
structures of curtains the essence of the melody of curtain combinations in music, the theory of intervals are highlighted. In the works of Abdurahman Jami's "Risolayi musiqi"Forabi, Ibn Sina, the means of numbers and proportions of the Ba'dlar are described in detail. Ilmu Te'lif preliminary concept The Musical and physical properties of the sound, the acoustic properties of the sound, that is, the relationship between the volume of the vibrating body and the loudness of the sound, are revealed by the example of various musical instruments, and the factors of mathematical expression of their quantifiers are fundamentally illuminated.